Assessment of heavy metal pollution in soil samples from a gold mining area in Osun State, Nigeria using proton-induced X-ray emission - A.A. Fagbenro (Elsevier, 2021)
This study identified and determined the concentration of heavy metal contaminants in Igun, Ijana-Gada and Igbadae gold mining sites using Particle Induced X-ray Emission (PIXE) technique. This was with a view to providing information on various heavy metal concentrations, potential sources of metals contamination and pollution load at Igun, Ijana-Gada and Igbadae gold mining sites.A total of thirty soil samples were collected randomly from Igun, Ijana-Gada and Igbadae gold mining sites in the Ilesha area, Osun State. Twelve samples were collected each from Igun and Ijana-Gada sites; while six samples were collected from Igbadae site. The soil samples were processed and analyzed for selected heavy metals (Fe, Mn, Cu, Zn, Cr, M, V and Fe). A Multivariate statistics approach (Pearson Correlation Matrix and Principal Component Analysis) was used on the data for identification of contamination sources.The heavy metal concentrations in the studied soils decreased in the following order: Fe > Ti > Mn > V > Cr > Zn > Pb > Cu with mean value of Fe (84,470.60 mg/kg), Ti (15,337.30 mg/kg), Mn (576.80 mg/kg), V (465.90 mg/kg), Cr (304.10 mg/kg), Zn (103.90 mg/kg), Pb (38.60 mg/kg), and Cu (26.00 mg/kg). The result obtained from the assessment of heavy metal pollution using Enrichment Factor (EF), Pollution Load Index (PLI), and Pollution Index (PI) confirmed that Igun, Ijana-Gada, and Igbadae soils/mine-tailings were polluted in the range from slightly through moderately polluted up to highly polluted. Principal Component Analysis (PCA) extracted three major components: PC1with loading of Fe, V, Zn, and Cu, PC2 with high loading of Ti and Mn while PC3 with the contribution of Pb and Cr. This was corroborated by Pearson Correlation Matrix (PCM) for the analyzed elements.The study revealed that the soils and mine tailings from the study area were polluted with heavy metals especially V, Ti and Cr from anthropogenic sources with little crustal material contributions thereby posing serious environmental and health concerns.